The neuropeptide SIFamide modulates sexual behavior in Drosophila. - Terhzaz, S; Rosay, P; Goodwin, S; Veenstra, J (2007)
The expression of Drosophila neuropeptide AYRKPPFNGSIFamide (SIFamide) was shown by both immunohistology and in situ hybridization to be restricted to only four neurons of the pars intercerebralis. The role of SIFamide in adult courtship behavior in both sexes was studied using two different approaches to perturb the function of SIFamide; targeted cell ablation and RNA interference (RNAi). Elimination of SIFamide by either of these methods results in promiscuous flies; males perform vigorous and indiscriminant courtship directed at either sex, while females appear sexually hyper-receptive. These results demonstrate that SIFamide is responsible for these behavioral effects and that the four SIFamidergic neurons and arborizations play an important function in the neuronal circuitry controlling Drosophila sexual behavior.